2023
DOI: 10.2196/47735
|View full text |Cite
|
Sign up to set email alerts
|

The Role of Novel Digital Clinical Tools in the Screening or Diagnosis of Obstructive Sleep Apnea: Systematic Review

Abstract: Background Digital clinical tools are a new technology that can be used in the screening or diagnosis of obstructive sleep apnea (OSA), notwithstanding the crucial role of polysomnography, the gold standard. Objective This study aimed to identify, gather, and analyze the most accurate digital tools and smartphone-based health platforms used for OSA screening or diagnosis in the adult population. Methods We p… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 65 publications
0
1
0
Order By: Relevance
“…A systematic review showed that the digital clinical tools to screen or diagnose OSA demonstrated an excellent discriminating capability, with the best tools reaching an area under the curve of > 0.99)[ 21 ]. Of the 41 studies covered in the systematic review (Table 1 ), 11 (27%) used bed/mattress sensors, 10 (24%) used wearables, 7 (17%) used smartphones, 5 (12%) used nasal airflow sensors, and 8 (20%) could not be classified into either of these[ 21 ].…”
Section: Use Of Technology For Diagnosis Of Sleep Disordersmentioning
confidence: 99%
“…A systematic review showed that the digital clinical tools to screen or diagnose OSA demonstrated an excellent discriminating capability, with the best tools reaching an area under the curve of > 0.99)[ 21 ]. Of the 41 studies covered in the systematic review (Table 1 ), 11 (27%) used bed/mattress sensors, 10 (24%) used wearables, 7 (17%) used smartphones, 5 (12%) used nasal airflow sensors, and 8 (20%) could not be classified into either of these[ 21 ].…”
Section: Use Of Technology For Diagnosis Of Sleep Disordersmentioning
confidence: 99%
“…As the detection of SDB with polysomnography is cost-and time-intensive, a widespread screening for SDB is currently not feasible. However, the implementation of wearable and artificial intelligence-based devices for screening of SDB is an interesting and growing field in development and research [114,115] that warrants further exploration and scientific validation. If indicated, treatment of SDB should be initiated and followed up closely to ensure optimal therapy adherence.…”
Section: Conclusion and Future Perspectivesmentioning
confidence: 99%